2017
DOI: 10.1038/srep46687
|View full text |Cite
|
Sign up to set email alerts
|

Tissue accumulation of microplastics in mice and biomarker responses suggest widespread health risks of exposure

Abstract: Microplastics (MPs) are a significant environmental health issue and increasingly greater source of concern. MPs have been detected in oceans, rivers, sediments, sewages, soil and even table salts. MPs exposure on marine organisms and humans has been documented, but information about the toxicity of MPs in mammal is limited. Here we used fluorescent and pristine polystyrene microplastics (PS-MPs) particles with two diameters (5 μm and 20 μm) to investigate the tissue distribution, accumulation, and tissue-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
580
4
24

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 794 publications
(620 citation statements)
references
References 49 publications
(68 reference statements)
12
580
4
24
Order By: Relevance
“…The same group has now reported a similar analysis in a mammalian species (Deng et al, 2017). Ingested by the mice through drinking water, 5 and 20 µm polystyrene micro-particles elicited somewhat similar pathological and physiological changes in mice.…”
Section: Microplastics Ingestion and Adverse Effects In Mousementioning
confidence: 53%
See 2 more Smart Citations
“…The same group has now reported a similar analysis in a mammalian species (Deng et al, 2017). Ingested by the mice through drinking water, 5 and 20 µm polystyrene micro-particles elicited somewhat similar pathological and physiological changes in mice.…”
Section: Microplastics Ingestion and Adverse Effects In Mousementioning
confidence: 53%
“…On the whole, the findings of Deng et al (2017) were made under conditions that mimic a massive overdose of microplastics and the results seen are limited to what might resemble a tissue limited acute inflammatory response. Documenting the fact that such responses could be elicited by the presumably chemically inert pristine microplastics is not without value, but the suggestion of "widespread health risks of (microplastics) exposure" cannot be taken without some reservations.…”
Section: Implications and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper, Yongfeng Deng and colleagues have analyzed the uptake of 5 µm and 20 µm polystyrene particles in mice and have monitored exposure-associated consequences with a focus on energy and lipid metabolism. The authors conclude that their data suggest widespread health risks of exposure to microplastic particles (Deng et al 2017).…”
mentioning
confidence: 92%
“…More recently, Lu et al [21] showed that the freshwater fish Danio rerio (zebrafish) exhibited a higher oxidative stress status after seven days of exposure to polystyrene MP, revealed by increased SOD and catalase (CAT) activities. Deng et al [22] tested the effect of fluorescent polystyrene MP in mice, revealing increased activities for SOD and GPx and decreased CAT activity, signifying the potential health risk MPs represent to biota. Nevertheless, only a few of these studies report on the physiological effects of MP exposure in biota from aquatic environments, where MP abundance is most often reported [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%